2011
DOI: 10.1158/1055-9965.epi-10-1219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aerobic Exercise on Premenopausal Sex Hormone Levels: Results of the WISER Study, a Randomized Clinical Trial in Healthy, Sedentary, Eumenorrheic Women

Abstract: Background It is hypothesized that exercise can lead to a decrease in breast cancer risk through several hormonal and non-hormonal mechanisms. The Women in Steady Exercise Research (WISER) study investigated the effects of aerobic exercise on premenopausal sex hormone levels. Methods 391 sedentary, healthy, young eumenorrheic women were randomized into an exercise intervention of 30 minutes of aerobic exercise 5 times a week for approximately 16 weeks (n=212), or into a control group (n=179). Serum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
(38 reference statements)
1
27
0
1
Order By: Relevance
“…We specifically used baseline data only from subjects who completed the Women in Steady Exercise Research (WISER) study, the primary purpose of which was to assess the effect of an exercise intervention on parameters associated with breast cancer risk (11, 12). As previously reported, the exercise intervention had no significant effect on SHBG or sex hormone concentrations despite significant increases in aerobic fitness and lean body mass, and a significant decrease in percent body fat (13, 14), possibly because overall the body composition changes that did occur were modest in degree.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We specifically used baseline data only from subjects who completed the Women in Steady Exercise Research (WISER) study, the primary purpose of which was to assess the effect of an exercise intervention on parameters associated with breast cancer risk (11, 12). As previously reported, the exercise intervention had no significant effect on SHBG or sex hormone concentrations despite significant increases in aerobic fitness and lean body mass, and a significant decrease in percent body fat (13, 14), possibly because overall the body composition changes that did occur were modest in degree.…”
Section: Introductionsupporting
confidence: 57%
“…Serum concentrations of T, E 2 , estrone sulfate, progesterone, and SHBG were measured using commercially available RIA kits for sex steroids and an ELISA for SHBG as previously described (13). Bioavailable fractions of T and E 2 were calculated using the equations of Vermeulen et al (16) and association constants estimated by Mazer (17).…”
Section: Methodsmentioning
confidence: 99%
“…Despite these encouraging results, there remains some controversy regarding the effect of exercise and hormone levels in premenopausal women. For instance, in the 16-week WISER study, no significant differences in sex hormones or SHBG were demonstrated between exercise and sedentary groups (Smith et al, 2011). The results of the study involving the high-risk premenopausal women may be due to the increased length of the study, the performance of vigorous activity opposed to moderate exercise, or the doubled duration of physical activity compared with the WISER study.…”
Section: Physical Exercisementioning
confidence: 87%
“…For women, cyclic hormonal variations can influence the aspects of health and health behavior, from smoking cessation efficacy to physiological responses to exercise. Various studies have been conducted to demonstrate the effects of female sex hormones during isotonic exercise, [10][11][12] but none have investigated the effects of the same during isometric exercise. [13] Hence, the present study has been planned to assess the role of gonadal steroids (estrogen and progesterone) on bronchial lability under resting conditions and when exposed to a simple isometric exercise (handgrip), at different phases of the menstrual cycle.…”
Section: Original Articlementioning
confidence: 99%